The Role of Context in Graphic Design (Al-Academy, 2023)
The need for an intellectual understanding of the context from many aspects' dictates understanding the ways through which the graphic designer walks in simulating the intent of the design process and elevating it to levels of communicative perception that leads to communicating the idea to the recipient, and it is thus a need closely related to the context, if it is historical. Culturally or socially, and between the mechanisms of selecting and operating the elements and units of the graphic and design achievement. On this basis, the role of context in graphic design can be studied.The research included four chapters, the first chapter of the research problem and the need for it, and the aim of the research was (discovering the role of context in graphic design), and then the importance of the research. As for the second chapter, it included the theoretical framework, and it may consist of two chapters, the first is (the concept of context and its types), and the second chapter is (context in design), and then the third chapter (research procedures), as the researchers adopted the descriptive approach as a way to analyze the content, based on what emerged The theoretical framework of the indicators, and then the research sample was intentionally chosen, for models of global slogans, to achieve the goal of the research, and then the research came out with results and conclusions, including:1- Following the historical context in designing logos resulted in belonging to the inherited ideas of each time period and embodying them within their temporal transformations, and this appeared in the two models.2- Employing shorthand treatment, specifically in the first model, led to achieving ease of reception.